Magnetic Solid Phase Extraction Based on Nanostructured Magnetic Porous Porphyrin Organic Polymer for Simultaneous Extraction and Preconcentration of Neonicotinoid Insecticides From Surface Water - Selahle, Shirley K.; Waleng, Ngwako J.; Mpupa, Anele; Nomngongo, Philiswa N. (Frontiers in Chemistry, 2020)
In this study, a magnetic porphyrin-based porous organic polymer (MP-POP) nanocomposite was successfully synthesized according previous studies and applied as an adsorbent for simultaneous extraction and preconcentration of four neonicotinoid insecticides from surface river water. The MP-POP was characterised using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy/energy dispersive x-ray spectroscopy (SEM/EDS), N2-adsorption/desorption analysis, Fourier Transform infrared spectroscopy (FTIR). The neonicotinoid insecticides were quantified using high performance chromatography coupled with diode array detector (HPLC-DAD). The MP-POP shown to have a high surface area, highly porous structure and strong affinity towards the investigated analytes. The adsorption capacities were 99.0, 85.5, 90.0 and 79.4 mg g−1 for acetamiprid, clothiandin, thiacloprid and imidacloprid, respectively. The influential parameters affecting the magmatic µ-solid phase extraction (M-µ-SPE) procedure were investigated using fractional factorial design and surface response methodology (RSM). Under optimum conditions, the method exhibited relatively low limit of detection in the range of 1.3-3.2 ng L−1, limit of quantification in the range of 4.3-11 ng L−1 and wide linearity (up to 600 µg L−1). The intraday and interday precision, expressed as the relative standard deviation (RSD) were less than 5%. The percentage recoveries for the four target analytes ranged from 91-99.3% for the spiked river water samples. The method was applied for determination of neonicotinoids in river water samples and concentrations ranged from 0-190 ng L−1.